Research status and development trend of optical communication technology - Xiangdong LV; Xuerui LIANG; Qianchen YU; Weidong MA (Dianxin kexue)
With the rapid growth of network bandwidth demand and the development of new applications and network services,the development of optical networks is facing a huge bottleneck of transmission capacity,switching granularity and network control.In order to solve these problems,researchers around the world have put forward new solutions.The technological innovation in optical networks in recent years was discussed,the development of dynamic reconfigurable optical network,integrated optoelectronics and optical fiber transmission technology was mainly discussed,and the future development trend of optical networks was analyzed in order to provide reference for related research.